TRANSPARANSI DAN PENGUNGKAPAN LAPORAN KEUANGAN BANK SYARIAH: KAJIAN LITERATUR SISTEMATIS - Muffida Hani Pohan; Sri Muliani; Siti Adzkiah Khairunnisa; Akmal Huda Nasution; Sakina Balqis; Chairunnisa Zakina Adibra (CV. Denasya Smart Publisher, 2026)
Transparency and disclosure of financial reports are key pillars in maintaining accountability and public trust in Islamic banking institutions. This study aims to systematically review the literature related to the practices of transparency and disclosure of Islamic bank financial reports, identify factors that influence disclosure quality, and map research gaps that still need to be explored. The method used is a Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, through a search of Scopus, Web of Science, and Google Scholar databases in the 2010–2024 period. A total of 35 articles that meet the inclusion criteria are analyzed in depth. The results of the study indicate that the level of Islamic bank disclosure is influenced by internal factors such as bank size, profitability, ownership structure, and the existence of a Sharia Supervisory Board (DPS), as well as external factors such as financial authority regulations, stakeholder pressure, and the level of development of a country's capital market. Furthermore, it was found that Sharia-based disclosure standards—as issued by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI)—have not been consistently applied across jurisdictions. This study provides a theoretical contribution to enriching understanding of the accountability of Islamic financial institutions, while also providing practical implications for regulators, bank management, and investors in improving the quality of Sharia-compliant financial reporting.